"It's a Shadow Life": Zadie Smith's Swing Time (Papers in Arts and Humanities, 2024)
Shadow and limelight constantly, often imperceptibly change places in Zadie Smith’s 2016 novel Swing Time. This is a fictional world where the narrator/main character can never become a true protagonist, and her namelessness gives her both universality and invisibility.  Appearances deceive, success and failure are not separated, and binaries are questioned, even erased. Zadie Smith is a young English novelist born to a Jamaican mother and an English father; she spent her childhood and early adulthood in Northwest London—a place defined by hybridity and poverty—and recently moved to New York. Her oeuvre to date is a complex insight into questions of race, friendship, personal identity, belonging, and other issues, all connected to life in a globalized world. Her Swing Time presents a mature, objective outlook on various lives connected through race, dance, and fates. Zadie Smith’s latest novel is a representative work of literature for tracing the manifestations of (in)visibility in a globalized world. This novel builds on visuality: movies, songs, and dances from the swing era come to life, it features a Madonna-like international pop star and two young protagonists who attempt to define themselves through dance. Here the visible and the invisible are interlinked, and superior and inferior are interchangeable. The novel actively challenges readers’ preconceived notions of character, good and bad, progression and degression, and it prompts an unbiased look at the fates of its various characters. The investigation of the ways the visibility–invisibility binary is redefined through the novel leads us to a view into current social phenomena, such as race in a global world, (post-) diaspora, minorities, class hierarchy, political agency, mobility, and identity.
Keywords: literature; race; mobility; cosmopolitanism; identity